2016
DOI: 10.1002/jbt.21773
|View full text |Cite
|
Sign up to set email alerts
|

β‐Carotene Induces Apoptosis in Human Esophageal Squamous Cell Carcinoma Cell Lines via the Cav‐1/AKT/NF‐κB Signaling Pathway

Abstract: β-carotene, a type of terpenoid, has many metabolic and physiological functions. In particular, β-carotene has an antitumor effect. However, the efficacy of β-carotene against esophageal squamous cell carcinoma (ESCC) remains unclear. In our study, β-carotene inhibited the growth of ESCC cells and downregulated expression of the Caveolin-1 (Cav-1) protein. Cav-1 protein was expressed only in ESCC cells, not in Het-1A cells. Moreover, β-carotene triggered apoptosis, induced cell cycle G0⁄G1 phase arrest, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…It is well ingrained that cancerous cells have ability of evade apoptosis which is a hallmark of cancer [51]. Our results validated the recent finding suggested that β-carotene has anti-tumor potential and inhibits the growth of esophageal squamous cell carcinoma (ESCC) ESCC cells and eventually induces apoptosis [31]. To assess whether the inhibition of CAMKIV by β-carotene has any effect on cell apoptosis, HuH7 and HEK293-T cell lines were incubated with β-carotene with increasing concentration.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is well ingrained that cancerous cells have ability of evade apoptosis which is a hallmark of cancer [51]. Our results validated the recent finding suggested that β-carotene has anti-tumor potential and inhibits the growth of esophageal squamous cell carcinoma (ESCC) ESCC cells and eventually induces apoptosis [31]. To assess whether the inhibition of CAMKIV by β-carotene has any effect on cell apoptosis, HuH7 and HEK293-T cell lines were incubated with β-carotene with increasing concentration.…”
Section: Discussionsupporting
confidence: 93%
“…Here, we used a natural compound β-carotene, a member of the carotenoid family, which has antioxidant activity and could rescue the risk of certain cancers [30]. Recent studies suggested that β-carotene has anti-tumor potential and inhibits the growth of esophageal squamous cell carcinoma cells and eventually induces apoptosis [31]. β-carotene also showed anti-cancer stem cells activity in neuroblastoma [32].…”
Section: Introductionmentioning
confidence: 97%
“…The antioxidant properties of β -carotene have been demonstrated in previous studies (Obulesu et al, 2011;Zhu et al, 2016). We demonstrated that in TBI mouse models, β -carotene could (1) to a certain degree, reduce brain injury and improve neurological function after TBI (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…The molecular mechanism of carotenoids in isolated human cell culture has been studied in some details. These studies have shown that carotenoids exert their protective effect through following mechanisms: 1) causing cell cycle arrest in G1/G0 phase by down-regulating the levels of Cyclin D1 (Malumbres et al, 2009); 2) induction of apoptosis by down-regulating the levels of Survivin (Kato et al, 2001;Zhu et al, 2016); 3) enhanced cellular gap junction communication (Bertram et al, 2004) and 4) anti-angiogenic effect through modulation of various cytokines (decreased levels of IL-6, IL-1b, TNF-a, and GM-CSF and increased level of IL-2 and TIMP-1) (Guruvayoorappan et al, 2007). We did not study the mechanism of cellular inhibition and induction of DNA damage by carotenoids in our cell cycle.…”
Section: Discussionmentioning
confidence: 99%